2019
DOI: 10.1108/jhlscm-12-2018-0081
|View full text |Cite
|
Sign up to set email alerts
|

A multi-objective emergency network design problem to carry out disaster relief operations in developing countries

Abstract: Purpose One of the problems in post-earthquake disaster management in developing countries, such as Iran, is the prediction of the residual network available for disaster relief operations. Therefore, it is important to use methods that are executable in such countries given the limited amount of accurate data. The purpose of this paper is to present a multi-objective model that seeks to determine the set of roads of a transportation network that should preserve its role in carrying out disaster relief operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…One of the problems of post-earthquake crisis management in developing countries such as Iran is the forecast of the available transportation network for crisis relief operations. Babaei et al (2019) proposed a mathematical programming model with three main objectives of minimizing total travel time, total network length and maximum coverage of emergency areas for effective earthquake rescue operations. The results of the model implementation in the Tehran highway network showed that the minimum possible length for the emergency transport network is almost half of all its main roads.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the problems of post-earthquake crisis management in developing countries such as Iran is the forecast of the available transportation network for crisis relief operations. Babaei et al (2019) proposed a mathematical programming model with three main objectives of minimizing total travel time, total network length and maximum coverage of emergency areas for effective earthquake rescue operations. The results of the model implementation in the Tehran highway network showed that the minimum possible length for the emergency transport network is almost half of all its main roads.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This model is considered a weighting and payment system to find the best plan. Babaei et al (2019) considered the total travel time of emergency trips, the total length of the network and the provision of coverage to the According to the literature review, many papers considered a single objective in their proposed models. Some papers presented a multi-objective model regardless of the priority of the objective functions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Babaei et al [2] incorporate the total time spent on emergency travels, the total network length, and the coverage extent to emergency demand/supply points into a multiobjective integer linear programming model. e most recent paper in this field, Nikoo et al [10], suggests a largescale emergency network design problem considering earthquake scenarios in the metropolis of Tehran.…”
Section: Emergency Road Network Designmentioning
confidence: 99%
“…In such cases, even less severe earthquakes may lead to extensive damages [1]. Lack of proper access to disaster relief centres in the city (spatially and temporally) is one of the most important causes of human disasters is lack of access can be seen when damage to all or a section of the road network makes efficient use of the remaining network impossible [2][3][4]. Rescue and relief missions are difficult due to earthquake-induced chaos, road network use for city clearance, and uncoordinated public assistance.…”
Section: Introductionmentioning
confidence: 99%